Population dynamics of Alternaria solani, Cercospora beticola, Ramularia beticola, and Stemphylium beticola in residues of host crops, non-host crops, and weeds in Dutch rotation systems - Köhl, Jürgen; Elena, Georgina; Hanse, Bram; Houwers, Ilse; Groenenboom-de Haas, Lia; de Lange, Ezra; Verstegen, Harry; Evenhuis, Albartus (Frontiers in Agronomy, 2024)
Crop residues colonized saprophytically by necrotrophic plant pathogens are an important primary inoculum source for epidemics of foliar diseases. Residues of crops, weeds, and litter were systematically sampled in a complex crop rotation experiment. Concentrations of DNA of major pathogens of the grown crops, Alternaria solani in potato and Cercospora beticola, Ramularia beticola, and Stemphylium beticola in sugar beet, were quantified in the residues using newly developed qPCR assays. Repeated field trials gave additional insights into the dynamics of A. solani in potato foliage residues for 2 years. The overall results demonstrate that the A. solani and C. beticola colonized crop residues of their host crops initially after harvest at high densities whereas R. beticola and S. beticola were almost absent in the field. Within several months, amounts of available host residues decreased substantially and concentrations of pathogens in the remaining host residues decreased steeply. Alternative substrates, residues of non-host crops including cover crops and weeds, were colonized saprophytically by the necrotrophic pathogens A. solani and C. beticola. It can be concluded that residues of non-hosts can potentially serve as an important bridge for pathogen populations during host-free cropping seasons in crop rotation systems. These findings contribute to the development of rational crop residue management strategies aiming at disease prevention by lowering the inoculum potential in crop rotation systems.